Hubungan Usia dan Konsumsi Makanan Berlemak dengan Kolesterol Total Pada Lansia Kelurahan Serengan Surakarta - Adhiyani, Cisillia (Jurnal Farmasi (Journal of Pharmacy), 2013)
Aging brings physical decline and increases morbidity trend, out of many is coronary heart disease(CHD). This disease is the leading cause in Indonesian’s total death number and one of the risk factors is hypercholesterolemia. Hypercholesterolemia is influenced by diet, heredity, age, sex, obesity, stress, alcohol, and physical activity. To identify the relationship of age and consumption of fatty food by total cholesterol. It is a descriptive analytical research by applying cross sectional approach. Purposive sampling method is conducted. Data are analyzed using SPSS version 16.0 Result of taking 101 elderly as samples, 13 are male and 88 are female, 28 elderly female tend to have cholesterol increase. The age range of 55 – 64 years old has got the highest cholesterol level than the other age range. Elderly who like to consume fatty food are 21 compared to people who don’t like fatty food are only 8. Total cholesterol test result of 101 blood samples obtains 107 mg /dl for lowest level and 301 mg /dl for highest level with 184 mg /dl for average. Elderly with CHD risk are 19 people and high risk of CHD are 10 people based on the total cholesterol result. The result of the statistical analysis is concluded that there is significant association of age with total cholesterol (p=0.067,α=0.05), there is no significant association with the consumption of fatty foods in total cholesterol ( p=0.057 ; α=0.05 ), and there are no significant relationships of age, consumption of fatty foods with total cholesterol (p=0.185; α=0.05)